11th international Media Art Biennale WRO 05 = XI Miedzynarodowe Biennale Sztuki Mediow WRO 05. - Biennale Wroclaw 2005; Janicki, Pawel; Krajewska, Violetta (Wroclaw : WRO Center for Media Art Wroclaw, 2005)
AL + AL ; Arnold, Robert ; Bartana, Yael ; De Bemels, Antonin ; Bertrand, Yann ; Biggs, Simon ; Boord, Dan ; Borkowski, Pawel ; Brink, Jasper Van Den ; Bundi, Hercli ; Cappozzo, Alessandro ; Choi Wai-hung ; De Clerq, Anouk ; Czacki, Catherine ; DS-X.org ; Fletcher, Harrell ; Gonsior, Grzegorz ; Gustowska, Izabella ; Hannah, Adad ; Hayashi, Sachiko ; Henricks, Nelson ; Ho Tam ; Holba, Harald ; Holtom, Christopher ; Holzer, Derek ; Ina, Shinsuke ; Kisky Netmedia ; Kolster, Sara ; Kowner, Elyasaf ; Krenz, Igor ; Krzeczek, Dariusz ; Kurecki, Agata ; Kurokawa, Ryoichi ; Kushida, Takeshi ; Lanesey, Annmarie ; Lia ; Mackern, Brian ; Macmillan, Tim ; Mastrototaro, Michael ; Migliorin, Cezar ; Moyzes, Tamara ; Müller-Büsching, Börries ; Muth, David ; Niegoda, Jacek ; van Nuenen, Jan ; Örkeny, Ivan ; Pietsch, Oliver ; Pook, Lynn ; Portugaly, Orna ; Poutiainen, Miika ; Provost, Nicolas ; Ramishvili, Koka ; Richardson, Emily ; Riekels, Stefan ; Romero, Juan ; Roy, Niklas ; Rynard, Su ; Sasada, Shinji ; Sato Yamashita, Juliana ; Schnitt, Corinna ; Schreiner, Volker ; Serban, Damien ; Siu Chi-Man, Eric ; Soukup, Markus ; Stubbs, Mike ; Takahashi, Keiko ; Theys, Frank ; Todorovic, Vladimir ; Valdovino, Luis ; Veldhoen, Martijn ; Verbeek, Jan ; Vicente, Laurent ; visomat inc. ; WA9440 ; Wolkowicz, Kathrin Maria ; Woo Ling Ling ; Zajec, Edward
Engels
Pools
Exhibition. 11th international Media Art Biennale WRO 05. WRO Center for Media Art Wroclaw. 11.05.2005 - 15.05.2005.
boek